A polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity, preparation method and application thereof
By blending polybenzimidazole, polyionic liquid and heteropolyate imidazole salt, a composite ion membrane with high ion selectivity and high proton conductivity was prepared, which solved the problem of low ion conductivity of the existing membrane and improved the membrane Performance and application suitability.
Patent Information
- Application Number
- CN202411547023.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-01
AI Technical Summary
The existing polybenzimidazole ion film has a low ion conductivity, which affects its performance in practical applications.
Compound ionic membranes with high ion selectivity were prepared by blending polybenzimidazole, polyionic liquid and heteropolyate imidazole salts. The polyionic liquid has anionic and cationic groups on the repeating unit, combining the cage-like structure of the heteropoly acid imidazole salt and the imidazole group, which improves the electrical conductivity and mechanical strength of the film.
It achieves high ion selectivity and high proton conductivity, improves the mechanical strength and chemical stability of the membrane, and is suitable for flow batteries and high-temperature proton exchange membrane fuel cells.
Smart Images

Figure CN119069758B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ion membranes, and specifically relates to a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity, a preparation method and application thereof, especially application in liquid flow batteries and high-temperature proton exchange membrane fuel cells. Background Art
[0002] Polybenzimidazole was first widely used as a proton exchange membrane in fuel cells due to its excellent mechanical strength and temperature resistance. Its excellent chemical stability and extremely low cross-contamination also make it the most promising ion membrane material for flow batteries. However, there are still several key issues to be resolved, especially the low ion conductivity. Improving the ion conductivity of polybenzimidazole ion membranes without affecting ion selectivity and stability is the core task to achieve its practical application.
[0003] Based on the above reasons, this application is hereby filed. Summary of the invention
[0004] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity, its preparation method and application, to solve or at least partially solve the above technical defects existing in the prior art.
[0005] The polyionic liquid used in the present invention is a type of ionic liquid polymer having anionic and cationic groups on the repeating unit, which has the excellent properties of both ionic liquids and polymers. The ion membrane obtained by blending with polybenzimidazole has high conductivity, good mechanical strength, and excellent chemical stability. At the same time, in order to further improve the conductivity of the ion membrane, an imidazole salt of an oxygen-containing polyacid (heteropolyacid imidazole salt) is added to form a composite ion membrane. In addition, the preparation method of the present invention is simple in process, and the composite ion membrane obtained has high ion selectivity and stability, high mechanical strength, and still maintains high proton conductivity at high temperatures.
[0006] In order to achieve the above-mentioned purpose of the present invention, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity, the method specifically comprising the following steps:
[0008] The polybenzimidazole, polyionic liquid and heteropolyacid imidazole salt are dissolved in an organic solvent by a blending method to form a casting solution, which is then cast into a membrane to obtain the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane.
[0009] Further, in the above technical solution, the polybenzimidazole comprises one or more of the following formula-repeating units; wherein: n is 1 or greater, about 10 or greater, or about 100 or greater;
[0010]
[0011] Formula 1.
[0012] Furthermore, in the above technical solution, the polyionic liquid is prepared using formaldehyde, glyoxal and diamine monomers as main raw materials, and the specific method is as follows:
[0013] The diamine monomer, glyoxal, formaldehyde and deionized water are mixed according to a ratio, and the obtained mixed reaction liquid is heated to 100°C and refluxed for 3 hours; then, the obtained product is added dropwise to an aqueous solution rich in large-volume anions, and then stirred at room temperature for 8-12 minutes, and the obtained product is filtered, washed and dried to obtain the polyionic liquid.
[0014] Furthermore, in the above technical solution, the diamine monomer is p-phenylenediamine, o-phenylenediamine, m-phenylenediamine, naphthalene-1,4-diamine, 4-aminobenzylamine, 2-aminobenzylamine, 3-aminobenzylamine, butanediamine, pentamethylenediamine, hexamethylenediamine, heptamethylenediamine, octanediamine, oxadiamine, decanediamine, 1,5-diaminotea, 4,4-diaminodiphenyl sulfone, bis(4-aminophenyl)sulfide, 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-(ethylenedioxy)bis(ethylamine), 9,9-bis(4-aminophenyl)fluorene, 4,4-diaminodiphenylmethane, 3,4-diaminodiphenylmethane, 4,4-diaminotriphenylmethane, 4,4-diaminobenzophenone, 4.4-biphenylenediamine, or a mixture of the above.
[0015] Furthermore, in the above technical solution, the molar ratio of the diamine monomer, glyoxal and formaldehyde is 1:1:1.
[0016] Furthermore, in the above technical solution, the amount of the deionized water used may not be specifically limited, as long as the diamine monomer, glyoxal and formaldehyde can be uniformly and completely dissolved.
[0017] Furthermore, in the above technical scheme, the bulk anions in the aqueous solution of bulk anions are one or a mixture of methanesulfonate anions, trifluoromethanesulfonate anions, phosphate anions, monohydrogen phosphate anions, dihydrogen phosphate anions, bistrifluoromethylsulfonyl imide anions, bistrifluoromethylbenzenesulfonyl imide anions, hexafluorophosphate anions, tetrafluoroborate anions, phosphotungstate anions, phosphomolybdate anions, silicotungstate anions, and silicomolybdate anions.
[0018] Further, in the above technical solution, the heteropolyacid imidazole salt is prepared from heteropolyacid and organic base, and the specific method is as follows:
[0019] dissolving a heteropoly acid in deionized water to obtain a heteropoly acid solution;
[0020] dissolving an organic base in deionized water to obtain an organic base solution;
[0021] The organic base solution is slowly added dropwise to the heteropolyacid solution according to the ratio at 40-50° C., and the mixture is stirred for reaction for 1 hour to obtain the heteropolyacid imidazole salt.
[0022] Furthermore, in the above technical solution, the heteropoly acid is one or a mixture of phosphotungstic acid, silicotungstic acid, phosphomolybdic acid and silicomolybdic acid.
[0023] Furthermore, in the above technical solution, the organic base is one or a mixture of imidazole, pyridine, diazine, triazine, trimethylamine, triethylamine, triethanolamine, and 1-vinylimidazole.
[0024] Furthermore, in the above technical solution, the molar ratio of the heteropoly acid to the organic base is 1:3.
[0025] Furthermore, in the above technical solution, the mass ratio of the polybenzimidazole, the polyionic liquid and the heteropolyacid imidazole salt is 10:1:1 to 2:3:6.
[0026] Furthermore, in the above technical solution, the organic solvent is one or a mixture of methanol, ethanol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.
[0027] Furthermore, in the above technical solution, the solid content of the casting solution is 3wt% to 15wt%.
[0028] The second object of the present invention is to provide a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity prepared by the above method.
[0029] Furthermore, in the above technical solution, the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane
[0030] The thickness is 5μm to 75μm.
[0031] The third object of the present invention is to provide the use of the above-mentioned polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane or the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared by the above-mentioned method in liquid flow batteries and high-temperature proton exchange membrane fuel cells.
[0032] The present invention also provides a liquid flow battery, comprising the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane of the present invention or the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared by the above-mentioned method.
[0033] The present invention also provides a high-temperature proton exchange membrane fuel cell, comprising the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane of the present invention or the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared by the above method.
[0034] The mechanism involved in the present invention is as follows:
[0035] The present invention uses polyionic liquid to participate in the blending to improve the mechanical strength and proton conductivity of the ion membrane, and at the same time, the addition of heteropolyacid imidazole salt has a special cage structure that can store protons, and the imidazole group can further improve the proton conductivity while making the ion membrane have high ion selectivity.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane provided by the present invention has high ion selectivity and mechanical strength; the organic base groups in the structure can improve the proton conductivity of the ion membrane.
[0038] (2) The polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane of the present invention can be prepared by only blending, the preparation method is simple, the product batch stability is good, it is easy to achieve scale-up production, and the prepared composite ion membrane has high ion selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0040] Figure 1 is a stress-strain curve diagram of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared in Example 2 of the present invention;
[0041] Figure 2 (a), (b), and (c) are respectively graphs of the proton conductivity of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared in Examples 1-3 of the present invention applied to a high-temperature proton exchange membrane fuel cell. DETAILED DESCRIPTION
[0042] The invention discloses a preparation method and application of a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity, and the preparation process comprises the following steps: (1) preparing an imidazole-based polyionic liquid with formaldehyde, glyoxal and diamine monomers; (2) preparing a heteropolyacid imidazole salt with a heteropolyacid and an organic base; (3) dissolving polybenzimidazole, polyionic liquid and heteropolyacid imidazole salt in a solvent, and dissolving to obtain a uniform and stable casting solution; (4) casting the casting solution into a film, and drying to obtain a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane. The method of the invention has a simple operation process, and the prepared composite ion membrane has high ion selectivity, high proton conductivity and high mechanical strength.
[0043] The present invention is further described in detail below through implementation cases.
[0044] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.
[0045] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0046] The aromatic ether polybenzimidazole (OPBI) used in the following Examples 1 and 3 of the present invention is synthesized by the method of Example 4 in the patent with authorization announcement number CN 116063679 B. The specific method is as follows:
[0047] (1) Add 3.90 g of phosphorus pentoxide to 25 mL of methanesulfonic acid (CAS No.: 75-75-2), heat at 120° C. with magnetic stirring for 5 h, dissolve and cool to room temperature to obtain a phosphorus pentoxide / methanesulfonic acid solution;
[0048] Add 20 mL of the pre-prepared phosphorus pentoxide / methanesulfonic acid solution to a 100 mL round-bottom flask, heat and stir to 40° C. under nitrogen protection; accurately weigh 5 mmol each of 4,4'-dicarboxy diphenyl ether and 3,3'-diaminobenzidine (the corresponding masses of both monomers are calculated based on the purity) and add them to the phosphorus pentoxide / methanesulfonic acid solution; stir and mix thoroughly to obtain a reaction precursor;
[0049] (2) transferring the reaction precursor to a microwave synthesizer, heating it under a microwave of a certain power, setting relevant program parameters for temperature increase reaction, and the reaction is carried out in two stages: first, the temperature is raised to 120° C. for reaction for 30 min, and then the temperature is raised to 150° C. for reaction for 20 min, and the microwave power is 500 W;
[0050] (3) After the reaction is completed, when the temperature of the reaction liquid drops to about 80° C., the reaction liquid is slowly poured into a glass beaker containing deionized water, the precipitated polymer is washed with water until it is nearly neutral, and then a saturated sodium bicarbonate solution is added for neutralization, and the mixture is filtered under reduced pressure, first washed with water for multiple times, and then washed with ethanol for multiple times, and the obtained polymer is vacuum dried at 120° C. for 24 hours, and ground into powder, i.e., the aromatic ether type polybenzimidazole.
[0051] The meta-fully aromatic polybenzimidazole (mPBI) used in the following Example 2 of the present invention is synthesized by the method of Example 3 in the patent with the authorization announcement number CN116063679 B. The specific method is as follows:
[0052] (1) Add 3.85 g of phosphorus pentoxide to 25 mL of methanesulfonic acid (CAS No.: 75-75-2), heat with magnetic stirring at 120° C. for 5 h, and cool to room temperature after dissolving to obtain a phosphorus pentoxide / methanesulfonic acid solution;
[0053] Add 20 mL of the pre-prepared phosphorus pentoxide / methanesulfonic acid solution to a 100 mL round-bottom flask, heat and stir to 40° C. under nitrogen protection; accurately weigh 5 mmol of isophthalic acid and 3,3'-diaminobenzidine (the corresponding masses of both monomers are calculated based on their purity) and add them to the phosphorus pentoxide / methanesulfonic acid solution; stir and mix thoroughly to obtain a reaction precursor;
[0054] (2) transferring the reaction precursor to a microwave synthesizer, heating it under a certain power of microwave, setting relevant program parameters for temperature rise reaction, and the reaction is carried out in two stages: first, the temperature is raised to 120° C. for reaction for 20 min, and then the temperature is raised to 160° C. for reaction for 40 min, and the microwave power is 300 W;
[0055] (3) After the reaction is completed, when the temperature of the reaction liquid drops to about 80° C., the reaction liquid is slowly poured into a glass beaker containing deionized water, the precipitated polymer is washed with water until it is nearly neutral, and then a saturated sodium bicarbonate solution is added for neutralization, and the mixture is filtered under reduced pressure, first washed with water for multiple times, and then washed with ethanol for multiple times, and the obtained polymer is vacuum dried at 120° C. for 24 hours, and ground into powder to obtain the meta-aromatic polybenzimidazole.
[0056] Example 1
[0057] The method for preparing a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity in this embodiment comprises the following steps:
[0058] (1) 3.2 g of 3-aminobenzylamine, 4 mL of acetic acid, 4.5 mL of 40% glyoxal solution, 2.5 mL of 40% formaldehyde solution and 10 mL of deionized water were mixed in a 100 mL round-bottom flask and refluxed at 100°C for 3 hours. Subsequently, the obtained product was added dropwise to a lithium dihydrogen phosphate aqueous solution and stirred at room temperature for about 10 min before precipitation. The obtained product was filtered and thoroughly washed with deionized water three times, and then dried under vacuum at 80°C to obtain a polyionic liquid.
[0059] (2) Take 100 g of phosphomolybdic acid and add it to 1 L of deionized water to obtain a phosphomolybdic acid aqueous solution; weigh 3 times the molar amount of imidazole used in the phosphomolybdic acid and dissolve it in 200 ml of deionized water to obtain an imidazole solution. Keep the phosphomolybdic acid aqueous solution in a constant temperature water bath at 45 °C, slowly add the imidazole solution dropwise, and stir the reaction for 1 h after the addition is completed to obtain phosphomolybdic acid imidazole salt.
[0060] (3) Weigh 2 g of aromatic ether polybenzimidazole, 0.8 g of the polyionic liquid prepared in step (1), and 0.4 g of phosphomolybdic acid imidazole salt prepared in step (2), respectively, dissolve them in 20 mL of N,N-dimethylformamide, and heat to 100° C. to obtain a casting solution with a solid content of 10%.
[0061] (4) The casting solution is cast into a membrane, and after drying, a composite ion membrane with a thickness of 40 μm is obtained.
[0062] Example 2
[0063] The method for preparing a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity in this embodiment comprises the following steps:
[0064] (1) 6.7 g of 2,2-(ethylenedioxy)bis(ethylamine), 4 mL of acetic acid, 5.5 mL of 40% glyoxal solution, 3.5 mL of 40% formaldehyde solution and 10 mL of deionized water were mixed in a 100 mL round-bottom flask and refluxed at 100°C for 3 hours. Subsequently, the obtained product was added dropwise to a lithium dihydrogen phosphate aqueous solution and stirred at room temperature for about 10 min before precipitation. The obtained product was filtered and thoroughly washed with deionized water three times, and then dried under vacuum at 80°C to obtain an imidazole-based polyionic liquid.
[0065] (2) Take 110g of phosphotungstic acid and add it to 1L of deionized water to obtain a phosphotungstic acid aqueous solution; weigh 3 times the molar amount of triazine used in the phosphotungstic acid and dissolve it in 200ml of deionized water to obtain a triazine aqueous solution. Keep the phosphotungstic acid aqueous solution in a constant temperature water bath at 45℃, slowly add the imidazole solution dropwise, and stir the reaction for 1h to obtain phosphotungstic acid imidazole salt.
[0066] (3) Weigh 2.5 g of meta-aromatic polybenzimidazole, 1.3 g of the polyionic liquid prepared in step (1), and 1 g of phosphotungstic acid imidazole salt prepared in step (2), respectively, dissolve them in 20 mL of dimethyl sulfoxide, and heat them to 100° C. to obtain a casting solution with a solid content of 12.5%.
[0067] (4) The casting solution is cast into a membrane, and after drying, a composite ion membrane with a thickness of 45 μm is obtained.
[0068] Example 3
[0069] The method for preparing a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity in this embodiment comprises the following steps:
[0070] (1) 8.5 g of 4,4-diaminotriphenylmethane, 4 mL of acetic acid, 5 mL of 40% glyoxal solution, 3 mL of 40% formaldehyde solution and 10 mL of deionized water were mixed in a 100 mL round-bottom flask and refluxed at 100°C for 3 hours. Subsequently, the obtained product was added dropwise to a lithium dihydrogen phosphate aqueous solution and stirred at room temperature for about 10 min before precipitation. The obtained product was filtered and thoroughly washed with deionized water three times and then dried in vacuum at 80°C to obtain an imidazole-based polyionic liquid.
[0071] (2) Take 80 g of silicotungstic acid and add it to 1 L of deionized water to obtain a silicotungstic acid aqueous solution; weigh 1-vinylimidazole in an amount 3 times the molar amount of the silicotungstic acid used and dissolve it in 200 ml of water to obtain a 1-vinylimidazole aqueous solution. Keep the silicotungstic acid aqueous solution in a constant temperature water bath at 45 °C, slowly add the 1-vinylimidazole aqueous solution dropwise, and stir the reaction for 1 h to obtain silicotungstic acid imidazole salt.
[0072] (3) Weigh 1.5 g of aromatic ether polybenzimidazole, 1 g of the polyionic liquid prepared in step (1), and 0.3 g of silicotungstate imidazole salt prepared in step (2), respectively, dissolve them in 20 mL of dimethyl sulfoxide, and heat to 100° C. to obtain a casting solution with a solid content of 7.5%.
[0073] (4) The casting solution is cast into a membrane, and after drying, a composite ion membrane with a thickness of 36 μm is obtained.
[0074] Performance Test:
[0075] The polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity prepared in Examples 1-3 was tested for proton conductivity, mechanical properties and ion selectivity, wherein:
[0076] 1. The specific test method of proton conductivity is as follows:
[0077] The proton conductivity involved in the application examples 1-3 of the present invention, that is, applied to the field of high-temperature proton exchange membrane fuel cells, is shown in Figure 2 The test method refers to Section 7 "Conductivity and Membrane Surface Resistance" of "Part 5: Proton Exchange Membrane Test Method" in GB / T42080-2023. The detailed test method is as follows:
[0078] a) Wet the inner chamber of the H-type conductivity cell with 3.0 mol / L H2SO4 solution;
[0079] b) Connect the two half slots of the H-type conductivity cell and press them tightly with an iron clamp. Add 3.0 mol / L H2SO4 solution into the conductivity cell and expel the bubbles. The liquid level should be higher than the circular hole of the half slot.
[0080] c) Clamp the test wires of the reference electrode and working electrode of the electrochemical workstation to the electrodes at both ends of the conductivity cell, and ensure that the distance between the electrodes on both sides and the membrane is the same; measure the impedance of the conductivity cell. After the test is completed, read the resistance value in the high-frequency region that intersects the real axis, which is the blank impedance R1 of the conductivity cell:
[0081] d) Place the pre-treated membrane sample between the two circular holes, repeat steps b) to c), and read the data, which is the impedance R2 of the conductivity cell with the membrane sample installed:
[0082] e) Repeat the measurement 8 times, record all impedance data and remove the highest and lowest values to calculate the average value, recorded as ,
[0083] f) Use a micrometer to measure the thickness of the film after the resistance measurement, record it as d.
[0084] Calculated by the formula:
[0085] a) Membrane resistance is calculated according to the formula as follows:
[0086] =
[0087] ——Membrane resistance, in ohms (Ω);
[0088] ——Impedance value of the conductivity cell with the membrane sample installed, in ohms (Ω):
[0089] The resistivity of a conductivity cell without a membrane sample installed, in ohms (Ω).
[0090] b) The membrane surface resistance is calculated according to the formula as follows
[0091] R A =R m A
[0092] R A —Film surface resistance, in ohm square centimeter (Ω•cm 2 ):
[0093] R m ——Membrane resistance, in ohms (Ω);
[0094] A——The effective area of the membrane, in square centimeters (cm 2 ).
[0095] c) The conductivity of the ion-conducting membrane is calculated according to the formula:
[0096]
[0097] σ——membrane conductivity, in Siemens per centimeter (S / cm);
[0098] R A —The film surface resistance is expressed in ohm square centimeters (Ω•cm 2 );
[0099] d is the average thickness of the film, in centimeters (cm).
[0100] Take 3 samples as a group and take the average value as the test result.
[0101] The proton conductivity involved in Application Example 3 of the present invention is applied to the field of all-vanadium redox flow batteries. The data are shown in Table 1. The test method refers to Section 5 "Proton Conductivity Test" of "Part 3: Proton Exchange Membrane Test Method" in GB / T20042.3-2009. The detailed test method is as follows:
[0102] Cut a film of a certain size as a sample, measure the thickness of the sample with a thickness gauge at a temperature of 25℃±2℃ and a relative humidity of 50±5%, and take the average value of three points as the value for calculating the thickness d. Fix the sample in a conductivity measurement fixture, and tighten the bolts with a torque wrench at a torque of 3N·m. Then place the conductivity measurement fixture in a constant humidity environment at different temperatures, and test it after keeping it constant for 30 minutes under each temperature and humidity condition. The impedance spectrum of the sample is measured with an electrochemical impedance tester under the conditions of a frequency range of (1~2×106 )Hz and a disturbance voltage of 10mV. In the measured impedance spectrum, read the impedance value (R) of the sample from the intersection of the high-frequency part of the spectrum line and the real axis.
[0103] The proton conductivity of the sample was calculated according to the following formula:
[0104] σ——proton conductivity of the sample, in Siemens per centimeter (S / cm);
[0105] a——the distance between the two electrodes, in centimeters (cm);
[0106] R——Measurement impedance of the sample, in ohms;
[0107] b——The effective length of the membrane in the direction perpendicular to the electrode, in centimeters (cm);
[0108] d is the thickness of the sample in centimeters (cm).
[0109] Take 3 samples as a group and calculate the average value as the test result.
[0110] (II) The specific test methods for mechanical properties are as follows:
[0111] a) Under constant temperature and humidity conditions of 25℃±2℃ and 50%±5%, quickly measure the thickness of the pretreated sample. The thickness and width of each sample should be measured at three points within the gauge length and the average value should be taken. The thickness measurement accuracy is ±0.2% and the width measurement accuracy is ±0.5%.
[0112] b) Place the sample in the test fixture of the tensile testing machine, make the longitudinal axis of the sample coincide with the center line of the upper and lower fixtures, and clamp it. The pressure value of the pneumatic fixture is selected within the range of 0.3MPa to 0.7MPa.
[0113] c) The tensile speed of the tensile testing machine is selected within the range of 50 mm / min to 200 mm / min.
[0114] d) After the sample breaks, read the corresponding load value. If the sample breaks outside the marked line, the test is invalid.
[0115] The required load and the corresponding film thickness and width are read according to the measured tensile curve, and the maximum tensile strength of the film is calculated according to formula (4).
[0116] The formula is: b =p / (b×d)
[0117] Where:
[0118] σ b ——The maximum tensile strength of the membrane, in megapascals (MPa);
[0119] p——maximum load, in Newton (N);
[0120] b——specimen width, in millimeters (mm);
[0121] d——specimen thickness, in millimeters (mm).
[0122] Take 3 samples as a group and calculate the average value as the test result.
[0123] (III) The specific test method for ion selectivity is as follows:
[0124] Ion selectivity S is the ratio of proton conductivity σ to vanadium ion permeability P
[0125] Calculation formula:
[0126] S——Ion selectivity of the membrane, unit is (S·min·cm -3 )
[0127] σ——Proton conductivity of the membrane, in Siemens per centimeter (S / cm);
[0128] P——Vanadium ion permeability of the membrane, in Siemens per centimeter (cm 2 ·min -1 );
[0129] Among them, the vanadium ion permeability detection method is as follows:
[0130] When using an H-type conductivity cell, add a mixed aqueous solution of 1.5 mol / L VOSO4 and 3.0 mol / L H2SO4 to the left chamber of the conductivity cell, and add a mixed aqueous solution of 1.5 mol / L MgSO4 and 3.0 mol / L H2SO4 to the right chamber, with the film sample to be tested separating the two chambers. During the test, take the solution on the right at regular intervals, detect its absorbance with a UV-visible spectrophotometer, and then substitute it into the standard curve of the relationship between vanadium ion concentration and absorbance to obtain the vanadium ion concentration.
[0131] The vanadium ion permeability P is obtained by fitting the following formula:
[0132] c L ———The initial concentration of vanadium ions in the left tank (mol / L);
[0133] c R (t)——the concentration of vanadium ions in the right tank at different times (mol / L);
[0134] A————Test area of membrane (cm 2 );
[0135] L——film thickness (cm);
[0136] V R ——The volume of the liquid in the right tank (mL);
[0137] t ——test time (min).
[0138] (IV) The specific test methods for antioxidant performance are as follows:
[0139] The antioxidant performance test should be carried out according to the following steps:
[0140] a) Cut a membrane fragment (5 cm × 5 cm) that has been soaked in 0.5 mol / L H2SO4 for 24 h, place it in an oven (105°C~110°C) and dry it until the difference between the two weighings is less than 0.2 mg. Weigh its mass on a balance as m o :
[0141] b) Place the dried membrane fragments into a beaker and add the prepared Fenton's reagent to ensure that the membrane is completely immersed. Then heat the beaker in a 60°C water bath and keep the constant temperature for 3 hours:
[0142] c) Take out the membrane and place it in a beaker filled with 3 mol / L dilute sulfuric acid aqueous solution. Soak it for 30 minutes and shake the beaker gently. Rinse the membrane sample with deionized water until the pH value of the water is neutral after washing.
[0143] Note: A pH of 7 using broad range pH paper is considered neutral.
[0144] d) Place the rinsed membrane in an oven (105°C~110°C) and dry it again until the difference between the two weighings is less than 0.2 mg. The mass is measured on a balance as m a .
[0145] The antioxidant properties of the membrane are characterized by comparing the mass changes of the dried membrane before and after the Fenton reagent treatment according to the following formula. The larger the value, the more serious the degradation of the polymer membrane during the Fenton reagent treatment, and the worse the antioxidant properties of the membrane. The antioxidant coefficient is expressed as S fm express.
[0146]
[0147] Where:
[0148] S fm —— Antioxidant coefficient measured by Fenton's reagent oxidation method, characterized by mass change;
[0149] m0——the mass of the dried membrane before Fenton’s reagent treatment;
[0150] m a —— Quality of dried membrane after treatment with Fenton's reagent.
[0151] Test result analysis:
[0152] Table 1
[0153]
[0154] The proton conductivity of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared in Examples 1-3 of the present invention and applied in the field of all-vanadium redox flow batteries is shown in Table 1. As can be seen from Table 1, the surface resistance of the composite ion membrane prepared in Example 1 of the present invention is 0.045Ω cm 2 The conductivity is 89 mS / cm, which meets the use requirements. The surface resistance of the composite ion membrane prepared in Example 2 of the present invention is 0.059 Ω cm 2 The conductivity is 76 mS / cm, which meets the use requirements. The surface resistance of the composite ion membrane prepared in Example 3 of the present invention is 0.039Ω cm 2 The conductivity is 108 mS / cm, which meets the use requirements.
[0155] Figure 1 is a stress-strain curve of the polybenzimidazole / polyionic liquid / heteropolyimidazole acid composite ion membrane prepared in Example 2 of the present invention; Figure 1 It can be seen that the mechanical strength of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared in Example 2 of the present invention can reach 52 MPa, and the elongation at break is 74%, which meets the use requirements.
[0156] Figure 2 The graph is a proton conductivity graph of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared in Examples 1-3 of the present invention applied to a high-temperature proton exchange membrane fuel cell; Figure 2 It can be seen that: Example 1, at a temperature of 160°C, its proton conductivity is as high as 245 mS / cm, which meets the use requirements. Example 2, at a temperature of 150°C, its proton conductivity is as high as 216 mS / cm, and at 160°C, the proton conductivity can also reach 199 mS / cm, which meets the use requirements. Example 3, at a temperature of 160°C, its proton conductivity is as high as 238 mS / cm, which meets the use requirements.
[0157] The ion selectivity of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared in Examples 1-3 of the present invention in the field of all-vanadium redox flow batteries is shown in Table 1. As can be seen from Table 1, the ion selectivity of the composite ion membrane prepared in Example 1 of the present invention is 6. 23×10 5 S·min·cm -3 , meeting the use requirements; the ion selectivity of the composite ion membrane prepared in Example 2 of the present invention is as high as 7.09×10 5 S·min·cm -3 , meeting the use requirements; the ion selectivity of the composite ion membrane prepared in Example 3 of the present invention is 5.22×10 5 S·min·cm -3 , meeting the usage requirements.
[0158] The antioxidant stability test results of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membranes prepared in Examples 1-3 of the present invention applied in the field of all-vanadium redox flow batteries are shown in Table 1. As can be seen from Table 1, the antioxidant performance of the composite ion membrane prepared in Example 1 of the present invention is 0, which meets the use requirements; the antioxidant performance of the composite ion membrane prepared in Example 2 of the present invention is 0, which meets the use requirements; the antioxidant performance of the composite ion membrane prepared in Example 3 of the present invention is 0, which meets the use requirements.
[0159] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0160] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention.
[0161] For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the protection of the present invention.
Claims
1. A method for preparing a polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane with high ion selectivity, characterized in that: The method specifically comprises the following steps: The polybenzimidazole, polyionic liquid and heteropolyacid imidazole salt are dissolved in an organic solvent by a blending method to form a casting solution, and the film is cast to obtain the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane; wherein: the polyionic liquid is prepared with formaldehyde, glyoxal and diamine monomers as main raw materials, and the specific method is as follows: the diamine monomer, glyoxal, formaldehyde and deionized water are mixed according to a ratio, and the obtained mixed reaction liquid is heated to 100°C and refluxed for 3 hours; then, the obtained product is added dropwise to an aqueous solution rich in large-volume anions, and then stirred at room temperature for 8-12 minutes, and the obtained product is filtered, washed and dried to obtain the polyionic liquid; the diamine monomer is any one of 3-aminobenzylamine, 2,2-(ethylenedioxy)bis(ethylamine) and 4,4-diaminotriphenylmethane; the molar ratio of the diamine monomer, glyoxal and formaldehyde is 1:1:1; The heteropolyacid imidazole salt is prepared from heteropolyacid and organic base, and the specific method is as follows: Dissolving a heteropoly acid in deionized water to obtain a heteropoly acid solution; the heteropoly acid is any one of phosphotungstic acid, silicotungstic acid, and phosphomolybdic acid; Dissolving an organic base in deionized water to obtain an organic base solution; the organic base is one of imidazole, triazine or 1-vinyl imidazole; Slowly drop the organic base solution into the heteropoly acid solution at 40-50° C. according to the ratio, and stir to react for 1 hour to obtain the heteropoly acid imidazole salt; The polybenzimidazole is an aromatic ether type polybenzimidazole OPBI or a meta-position fully aromatic type polybenzimidazole mPBI.
2. The preparation method according to claim 1, characterized in that: The bulk anions in the aqueous solution of the bulk anions are one or a mixture of methanesulfonate anions, trifluoromethanesulfonate anions, phosphate anions, monohydrogen phosphate anions, dihydrogen phosphate anions, bistrifluoromethylsulfonyl imide anions, bistrifluoromethylbenzenesulfonyl imide anions, hexafluorophosphate anions, tetrafluoroborate anions, phosphotungstate anions, phosphomolybdate anions, silicotungstate anions, and silicomolybdate anions.
3. The polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared by the method of claim 1 or 2.
4. Use of the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared by the method of claim 1 or 2 or the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane according to claim 3 in liquid flow batteries and high-temperature proton exchange membrane fuel cells.
5. A liquid flow battery or a high temperature proton exchange membrane fuel cell, characterized in that: The invention comprises the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane prepared by the method described in claim 1 or 2 or the polybenzimidazole / polyionic liquid / heteropolyacid imidazole composite ion membrane described in claim 3.
Citation Information
Patent Citations
A method for synthesizing high molecular weight polybenzimidazole compounds using microwave-assisted
CN116063679B
Modified nanometer material for improving stability of heteropoly acid in proton exchange membrane and preparation method thereof
CN106750051A
Polybenzoimidazole-poly (ionic liquid) cross-linked composite high temperature proton exchange membrane and preparation method thereof
CN107248583A